2009
DOI: 10.1177/0146167208325612
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Critical Cue: Implementation Intentions to Change One's Diet Work Best When Tailored to Personally Relevant Reasons for Unhealthy Eating

Abstract: Implementation intentions promote acting on one's good intentions. But does specifying where and when to act also suffice when goals involve complex change that requires not merely initiating a behavior but rather substituting a habit with a new response? In a pilot study and two experiments, the authors investigated the efficacy of implementation intentions to replace unhealthy snacks with healthy snacks by linking different types of cues for unhealthy snacking (if-part) to healthy snacking (then-part). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 43 publications
7
170
1
4
Order By: Relevance
“…Much of the debate on this issue was focused on whether pre-planning interventions should be 'content' free or whether the content should be guided or prompted by the researcher or practitioner facilitating the preplanning intervention. The general view was that eliciting individuals' personal rationales and obstacles in pre-planning interventions may be more effective as they provide person-centred reasons for developing future plans rather than externally-referenced reasons which may receive lower endorsement by the individual (Adriaanse et al, 2009;Verhoeven et al, 2014). However, as planning interventions tend to be as effective when imposed by the researcher or practitioner (Armitage, 2009) and individuals may not have the ability to identify appropriate cues, barriers, or obstacles, some felt that researcher-or practitioner-driven pre-planning interventions would be at least as, if not more, effective in developing planning expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the debate on this issue was focused on whether pre-planning interventions should be 'content' free or whether the content should be guided or prompted by the researcher or practitioner facilitating the preplanning intervention. The general view was that eliciting individuals' personal rationales and obstacles in pre-planning interventions may be more effective as they provide person-centred reasons for developing future plans rather than externally-referenced reasons which may receive lower endorsement by the individual (Adriaanse et al, 2009;Verhoeven et al, 2014). However, as planning interventions tend to be as effective when imposed by the researcher or practitioner (Armitage, 2009) and individuals may not have the ability to identify appropriate cues, barriers, or obstacles, some felt that researcher-or practitioner-driven pre-planning interventions would be at least as, if not more, effective in developing planning expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of planning and implementation intentions and the consistency in its effects notwithstanding, numerous questions remain. Meta-analyses have demonstrated that implementation intentions have medium-sized effects on behavioural outcomes in health contexts, but identified some heterogeneity in the effects (Adriaanse, Vinkers, De Ridder, Hox, & De Wit, 2011;BĂ©langer-Gravel, Godin, & Amireault, 2013;Carraro & Gaudreau, 2013;Gollwitzer & Sheeran, 2006;Kwasnicka et al, 2013) and there are a number of tests that have shown no effects of implementation intentions on behavioural enactment (Adriaanse, de Ridder, & de Wit, 2009;de Vet, Oenema, Sheeran, & Brug, 2009;Jackson et al, 2005;Leventhal, Diefenbach, & Leventhal, 1992;Lo et al, 2013;Michie, Dormandy, & Marteau, 2004).…”
Section: Recommendations From the Synergy Expert Group For Research Amentioning
confidence: 99%
“…In real life, and in previous studies on counterhabitual implementation intentions (e.g., Adriaanse et al, 2009;Webb et al, 2009), the habits that people aim to change usually relate to replacing unhealthy responses by more healthy responses, such as replacing chocolate by apples. Replacing chocolate by cookies might be easier than replacing chocolate by apples, as cookies may be more similar to chocolate in terms of their hedonic value than apples and may therefore already be more strongly linked to the critical situation.…”
Section: Discussionmentioning
confidence: 99%
“…For many behaviors, such as unhealthy snacking or drinking, identifying critical cues may be challenging as these cues may often reflect rather subjective internal states (e.g., "boredom" or "socializing") rather than clear-cut situational cues, such as time or place (e.g., "being at home"; Adriaanse et al, 2009). Identification of these subjective internal states as critical triggers for unhealthy behaviors requires substantial introspection, which many people may lack (Nisbett & Wilson, 1977).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Prior studies have generally observed that people can indeed identify and self-select suitable situations and responses (e.g., Adriaanse, de Ridder, & de Wit, 2009 ;Gollwitzer & BrandstĂ€tter, 1997 ). In fact, both experimenter-provided and self-generated implementation intentions have been shown to foster goal attainment effectively (Armitage, 2009 ).…”
Section: The Role Of Knowledge Accessibility In Planning and In The Cmentioning
confidence: 99%